Enhancing the efficiency and ambient stability of perovskite solar cells via a multifunctional trap passivation molecule. Issue 40 (4th October 2021) - Hossain, Maimur; Arunagirinathan, Rahul Narasimhan; Garai, Rabindranath; Gupta, Ritesh Kant; Iyer, Parameswar Krishnan
Abstract : The photovoltaic performance and ambient stability of perovskite solar cells were enhanced significantly through trap passivation by incorporation of a multifunctional additive molecule, 5-fluoropyrimidine-2, 4(1 H, 3 H )-dione (FPD). Abstract : In recent times the perovskite solar cells (PVSCs) have emerged as the most preeminent candidates among renewable technologies, yet the instability of PVSCs under ambient conditions has hindered their progress towards commercialization. Herein, a multifunctional passivation additive, 5-fluoropyrimidine-2, 4(1 H, 3 H )-dione (FPD), widely used as a cancer drug, was incorporated into the perovskite-based photoactive layer to enhance its photovoltaic efficiency along with its ambient stability. When this biologically active cancer drug molecule was utilized as a passivation additive, significant improvement was achieved in all the photovoltaic parameters, which collectively contributed to the enhancement of photovoltaic efficiency. The efficiency of PVSCs was elevated up to 20.22% for the FPD-passivated devices from 15.10% for the pristine device without any passivation. Furthermore, the incorporation of FPD also improved the long term durability of PVSCs by suppressing defects and enhancing the hydrophobicity of the perovskite surface. The FPD-passivated device maintained the PCE up to 89% in comparison to 27% for the pristine devices when PVSCs were exposed to a relative humidity of 45 ± 5% for 1000 h. This unique approach has elucidated the impact of passivation, which significantly enhanced the efficiency and long term stability to widen the possibility of practical applications.